The necessity oflegal arrangement of unit-linked life insurance products - Nikola Dacev (UTMS Journal of Economics, 2017)
The rapid development of life insurance and its dissemination throughout the world, and the emergence of new types of life insurance products, in order to meet the needs of citizens, raises the question of proper legal arrangement of these issues. This article refers to the life insurance products linked to investment funds (unit-linked life insurance products) as a new type of life insurance products, especially in developing countries. The purpose of this article is to explain the meaning and the types of unit-linked life insurance products offered by insurance companies; to provide the available statistical data regarding these types of insurance products; to analyze the legal framework of unit-linked life insurance products in the European Union and in some Southeast European countries, one member of EU and two candidates for EU membership. The conclusion of the article provides the reasons for additional legal regulation of the unit-linked life insurance products.
Keywords: K22; 330; policyholders; blue-chip stocks; investment funds; mutual funds; EU legal framework